Community perception on coastal resort development sitting in Malaysia Peninsular - Mat Raschid, Muhammad Yazah; Sharif, Roslina (Universiti Kebangsaan Malaysia, 2015)
The concept of coastal tourism includes the various ranges of tourism, leisure and recreational activities with provision of facilities and infrastructure to support the industry. This paper reports the findings of local community concerns toward the sitting of the three main resorts which are Malaysia’s premier resorts at a macro scale which results can represent the trend of other resorts in Malaysia. A case study of three premier resorts representing the northern, central and southern region of the West coast of Malaysian Peninsula which include Langkawi Island, Pangkor Island and Port Dickson while an depth interview of 40 interviewees from the local community in the three case study site were conducted. The investigation reveals that the sitting, design and construction of coastal resorts are done without the consent of the local communities thereby does not promote their custom, belief system and tradition. The paper gives clear understanding of the benefit or disadvantages of coastal tourism development to the local communities; it also presented views of the local community towards coastal resort developments in the three case study sites. The results presented could justify the selection of other case study sites towards enhancing tourists’ experience in coastal resort of the west Malaysia peninsula.